FUNGAL MAXILLARY SINUSITIS (ASPERGILLOSIS) IN A GERIATRIC PATIENT WITH DIABETES AND HYPERTENSION: A CASE REPORT - DR. BULBUL SAHU; DR. BHOOMI KASHYAP; DR. ANIK CHAKARBARTY; DR. SAUMYA JHA; DR. PANKAJ KUMAR (The Bioscan, 2026)
Aim: A case of maxillary aspergillosis with unusual clinical presentation and imaging findings. Background: The range of lesions and conditions that affect the maxillary sinus is wide and vast. This necessitates a dynamic multidisciplinary approach for proper diagnosis and effective management. Case description: We present an unusual case of maxillary aspergillosis was most consistent with lymphoma from the diagnostic imaging perspective. Histopathology and radiographically however, established the correct diagnosis; appropriate management commenced promptly. Conclusion: It is imperative that maxillary aspergillosis be diagnosed and managed properly and promptly to improve prognosis. Advanced imaging is required, but it plays an adjunct role to histopathology. Long-term follow-up is also necessary to ensure complete resolution of the infection Clinical significance: It is essential to correlate clinical and imaging results, and any discrepancies should be fixed right away to avoid postponing appropriate treatment. Histopathology frequently helps to establish a correct diagnosis and disputes any discrepancies.